1991
DOI: 10.1590/s0074-02761991000600040
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the antimalarial activity of plants of the Cucurbitaceae family

Abstract: Crude ethanolic extracts (CEEs) from two species of Cucurbitaceae, Cucurbita maxima and Momordica charantia (commonly called "abóbora moranga" and "melão de São Caetano", respectively) were assayed for antimalarial activity by the 4-d suppressive test. The CEE of dry C. maxima seeds showed strong antimalarial activity following oral administration (250 and 500 mg/kg), reducing by 50% the levels of parasitemia in Plasmodium berghei-infected mice. Treatment of normal animals with 500 mg/kg of the extract three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Munoz et al (2000) demonstrated moderate in vivo activity of MC extract against rodent malaria P. vinckei petteri 279. However, Amorim et al (1991) and Ueno et al (1996) did not observe in vitro antiplasmodial activity of ethanolic MC extract against P. berghei.…”
Section: Anthelmintic Studymentioning
confidence: 70%
“…Munoz et al (2000) demonstrated moderate in vivo activity of MC extract against rodent malaria P. vinckei petteri 279. However, Amorim et al (1991) and Ueno et al (1996) did not observe in vitro antiplasmodial activity of ethanolic MC extract against P. berghei.…”
Section: Anthelmintic Studymentioning
confidence: 70%
“…A literature study of these species revealed that only seven species, Alstonia bonei (Gandhi and Vinayak, 1990;Wright et al, 1993), Abrus precatorius (Limmatvapirat et al, 2004), Cassia occidentalis (Addae- Kyereme et al, 2001;Gasquet et al, 1993;Tona et al, 1999;Tona et al, 2001), Momordica charantia (Amorim et al, 1991;Munoz et al, 2000;Ueno et al, 1996), Nauclea latifolia (Azas et al, 2002;Benoit-Vical et al, 1998), Vernonia colorata (Benoit et al, 1996) and Vismia guineensis (Francois et al, 1999), had previously been investigated for antiplasmodial activity. To our knowledge, this is the first time that Annona muricata, Cola caricaefolia, Canna indica, Desmodium adscendens, Erigeron floribundus, Hoslundia opposita, Mitragyna ciliata, Olax subscorpioidea, Parkia biglobosa, Parketina nigrescens and Uvaria afzelii are being assessed for their antiplasmodial properties.…”
Section: Resultsmentioning
confidence: 99%
“…The water extract of Momordica foetida (Cucurbitaceae) was well tolerated and it delayed the development of P. berghei infection in C57BL mice (Waako et al 2005), the crude ethanolic extract of dry Cucurbita maxima seeds showed strong antimalarial activity following oral administration, reducing the levels of parasitemia in P. berghei-infected mice and the same extract of Momordica charantia was ineffective in lowering the parasitemic levels of malarious mice (Amorim et al 1991).…”
Section: Introductionmentioning
confidence: 99%